Hydrochemical assessment of surface water and groundwater quality along Uyyakondan channel, South India - Brindha, Karthikeyan; Kavitha, R. (Springer, 2015)
Groundwater and surface water quality is an important factor that determines its usage for drinking and irrigational use. This study was carried out along a major irrigation water source-Uyyakondan channel in Tiruchirappalli, south India. Fourteen surface water samples along the channel and fifteen groundwater samples close to the surface water sampling locations were collected to determine its suitability for drinking and irrigational purposes. Electrical conductivity, pH and concentrations of calcium, magnesium, sodium, potassium, carbonate, bicarbonate, chloride, sulphate, fluoride and nitrate were determined in the water samples. The chemical composition of the water samples were compared with the drinking water standards of World Health Organisation and Bureau of Indian Standards. Groundwater from this area was suitable for drinking based on magnesium, sulphate, bicarbonate, fluoride and nitrate, while the concentration of calcium, sodium, potassium and chloride exceeded the maximum permissible limits at few locations. Surface water was within the permissible limits for magnesium, potassium, bicarbonate, sulphate, fluoride and nitrate, while calcium, sodium and chloride exceeded the highest desirable limits. Sodium chloride was the dominant groundwater and surface water type. Irrigation water quality was assessed based on magnesium hazard, residual sodium carbonate, sodium percentage, sodium adsorption ratio, permeability index and salinity hazard. Water was suitable for irrigation based on magnesium hazard and residual sodium carbonate. Most water samples were doubtful for irrigation use based on sodium percentage and good for irrigation depending on sodium adsorption ratio. Though 60 % of groundwater and 29 % of surface water samples were suitable for drinking based on water quality index, majority of the water samples were not suitable for irrigation. The water quality in this area needs to be monitored regularly and it is crucial to treat the water before consumption.